Roland Barthes' Semiotics Representation In The Lyrics of The "Together Towards a New Normal" Campaign Advertisement - Feby Claudia Syawalia; Mauly Arzak Julika (Syntax Literate, 2022)
The pandemic has not ended since January 23, 2020, when Singapore confirmed its first case related to Covid-19 and until now there are still positive cases reported. It can be said that with all the preparations for handling and further strategies in dealing with the Covid-19 pandemic, Singapore is ready to adapt to Covid as an endemic and no longer a pandemic. Vaccination is the first step to reducing the risk of infection and transmission of Covid-19. During the socialization process of the Singaporean central government regarding vaccines for its citizens, many negative issues arose regarding the impact after the vaccine was injected. The government ordered that the rumors circulating be corrected and also cooperate with influencers in discussing vaccines again and clearing misunderstandings about the negative issues of vaccines that have been circulating previously. The strategic step that is now attracting the attention of many citizens and the media is related to public service advertisements inviting Singaporeans to vaccinate. The ad is part of the â€œIgotmyshotâ€ campaign, which is the Singapore government's official campaign to encourage citizens to get vaccinated so they can protect themselves and their loved ones as well as an effort to get back to normal socializing â€œa new normal lifeâ€. Purpose: This study was conducted to determine the meaning of semiotics in the song lyrics of the "Together Towards a New Normal" Campaign. Methods: The method used in this research is descriptive qualitative and uses Ronald Barthes' Semiotics theory. Implications: The results of this study indicate that the song lyrics in the advertisement "Together Towards a New Normal" can be interpreted through three stages of Ronald Barthes' sign. Based on the meaning of the message, an invitation to comply with the government's recommendations in following the entire series of protocols of life in the new era is denotatively contained in the entire stanza.